Perilaku Wanita Pekerja Seks Melakukan Konseling dan Tes HIV - Ruwayda Ruwayda; M Dody Izhar (Jurnal Ilmiah Universitas Batanghari Jambi, 2018)
The high prevalence of current HIV / AIDS problems is not only a health problem of infectious disease, but has become a very widespread public health problem, one of the high risk groups is Female Sex Workers (WPS). The number of female sex workers who counsel and test HIV in Rawasari Health Center is still low that is 27,67%. This research is quantitative research with cross sectional method, using Systematic Random Sampling technique with sample number 77 female sex worker. Instrument used questionnaire, analyzed by univariate analysis, bivariate and chi-square test. The result of the analysis of 77 respondents, 61% have bad behavior to do counseling of HIV test and 39% have good behavior do counseling of HIV test, 57,1% of respondents have low knowledge, 50,6% of respondents have unfavorable attitude and 50,6 respondents argue that the role of health workers is good for HIV counseling and testing. The result of bivariate analysis shows that there is significant correlation between knowledge (p-value = 0,000), attitude (p-value = 0,000) and the role of health officer (p-value = 0,013) with female sex worker conduct HIV counseling and testing at Payo Sigadung City of Jambi.It is hoped that health officers at Rawasari Puskesmas will improve direct and periodic counseling through information media, encourage and encourage female sex workers to conduct HIV counseling and testing.